THE EFFECT OF AUDIT TENURE, AUDIT FEE, AND SIZE OF PUBLIC ACCOUNTANT OFFICES ON AUDIT QUALITY (Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange 2014-2018) - Sembiring, Priscila Apriani; Sidharta, Juaniva; Sembiring, Caroline (Universitas Kristen Indonesia, 2021)
Audit quality is the most important thing that must be considered in the audit process, because of that the author needs to do research’s and the research’s was carried out with the purpose to knowing of audit tenure, audit fee, and size of audit firm. The samples of this research’s comes from a secondary to a manufacturing company and listed in Indonesia Stock Exchange during the period of the year 2014-2018. The author used research methods with quantitative analysis techniques, with data that is generated from annual financial reports on manufacturing companies. The results of this research’s showed that audit fee has a significant effect on audit quality. But, audit tenure and size of audit firm have not a significant effect. Testing the hypothesis used by linear regression analysis method with SPSS version 25.0 through. Keywords: audit quality, audit tenure, audit fee, and size of audit firm.